Biogeography meets taxonomy: Distribution-based inferences on the accuracy of identification and synonymization of East Asian earthworms - Shen, Huei-Ping (Zootaxa, 2018)
This paper demonstrates that the uniqueness of the geographical location of Taiwan and its adjacent islands can be taken as a basis to evaluate the accuracy of identification and synonymization of East Asian earthworms and further to clarify some disputes in earthworm taxonomy. A comprehensive review of the earthworm fauna from the Ryukyu Archipelago is given; as a result, two recorded species are recognized as new species, named here Amynthas ishigakiensis sp. nov. and Amynthas iriomotensis sp. nov. Common but harmful practices in earthworm taxonomy, synonymies with question marks and erection of sympatric subspecies, are commented.